Claws and consequences: human–tiger conflict and community responses in Bardiya National Park, Nepal - Shrestha, Prabina; Kadariya, Rabin; Subedi, Naresh; Paudel, Umesh; K.C., Rabin Bahadur (Frontiers in Conservation Science, 2025)
Human–tiger conflict (HTC) is one of the rising issues of Bardiya National Park (BNP) and is receiving attention from conservation biologists. This study emphasizes the extent of human–tiger conflict in two municipalities, Thakurbaba and Madhuban, in the buffer zone of Bardiya National Park, Nepal. Primary and secondary information was collected to determine the socio-economic characteristics relevant to tiger conservation following a questionnaire survey of the community people. A semi-structured questionnaire was randomly administered to 438 households to generate information from the respondents, along with these people’s perceptions toward tigers and their interest in tiger conservation. The Likert scale was used to assess respondents’ attitudes, while a chi-square test of homogeneity and logistic regression analysis were employed to determine the best-fitting model and identify significant variables influencing perceptions toward tiger conservation. A total of 18 people were killed and 10 were injured by tigers between 2019 and 2023. The people’s perception of tigers and their conservation was significantly associated with socio-economic variables, including gender, ethnicity, economic status, and source of income. We found female, low-income, and Janajati respondents likely to have negative attitudes toward their conservation. The Likert scale responses revealed strong overall support for tiger conservation and perceived tourism benefits. In addition to the ever-growing human–tiger conflict, people are aware of tiger conservation and suggest that making net wire fences, providing improved sheds for cattle, and cattle insurance schemes help to minimize Livestock depredation events; effective training on wildlife monitoring and awareness programs could be among the best ways to mitigate conflicts between humans and tigers.